Structural Form of Bridges Reflecting the Construction Processes (Fracture and Structural Integrity, 2018)
The structural form of a completed bridge is strongly affected by its structural form during construction. It follows that innovative construction processes sometimes produce innovative bridge designs. It is important to consider the construction process in conjunction with bridge design methods. This approach could be applied not only to new construction but also to replacements, reconstructions, or reinforcements. One of the authors has systematized the structural forms of bridges and clarified the principles underlying them. This paper aims to extend these principles to construction systems. In other words, changes in the structural systems of the construction processes and systematization of the relationship between a completed bridge and construction process in a design are illustrated. This systematization enables the application of a variety of conventional construction methods in a system. This would be helpful in developing new construction methods and designs for bridges.
Keywords: Systematization; Construction Process; Innovative Bridge Design